Bioinformatics - Baxevanis, Andreas D.; Bader, Gary D.; Wishart, David Scott (Hoboken, NJ : Wiley, 2020)
This fully revised Fourth Edition to a best-selling resource provides the reader with a hands-on guide to computational biology, primarily in the area of sequence analysis. The subject matter will cover a broad spectrum of concepts in bioinformatics, beginning with an overview of biological databases and ending with a series of chapters on predictive and comparative algorithms. Using relevant biological examples, the book will provide background on and strategies for using many of the most powerful and commonly-used algorithms for sequence-based discovery. Given the explosion in the number of organisms whose genomes have been sequenced over the last several years, the emergence of new types of data sets (particularly those derived using next-generation sequencing technologies), and increasing emphasis on being able to make effective use of "big data", the book is both timely and important to investigators in molecular biology and related fields. With a full-color, enlarged page design, this edition offers the most readable, up-to-date, and thorough introduction to the field for biologists. The new "Foundations" section insures that readers have a firm understanding of the technologies that generate the data, as well as the essential statistical and programming tools. Features include special boxes, enhanced use of real examples, and problem sets with answers provided on the book's dedicated website (www.wiley.com/bioinformatics). A glossary and appendix of sample file formats rounds out the book's reader-friendly, 'hands-on' treatment.
Biological sequence databases / Andreas D. Baxevanis -- Information retrieval from biological databases / Andreas D. Baxevanis -- Assessing pairwise sequence similarity : BLAST and FASTA / Andreas D. Baxevanis -- Genome browsers / Tyra G. Wolfsberg -- Genome annotation / David S. Wishart -- Predictive methods using RNA sequences / Michael F. Sloma, Michael Zuker, and David H. Mathews -- Predictive methods using protein sequences / Jonas Reeb, Tatyana Goldberg, Yanay Ofran, and Burkhard Rost -- Multiple sequence alignments / Fabian Sievers, Geoffrey J. Barton, and Desmond G. Higgins -- Molecular evolution and phylogenetic analysis / Emma J. Griffiths and Fiona S.L. Brinkman -- Expression analysis / Marieke L. Kuijjer, Joseph N. Paulson, and John Quackenbush -- Proteomics and protein identification by mass spectrometry / Sadhna Phanse and Andrew Emili -- Protein structure prediction and analysis / David S. Wishart -- Biological networks and pathways / Gary D. Bader -- Metabolomics / David S. Wishart -- Population genetics / Lynn B. Jorde and W. Scott Watkins -- Metagenomics and microbial community analysis / Robert G. Beiko -- Translational bioinformatics / Sean D. Mooney and Stephen J. Mooney -- Statistical methods for biologists / Hunter N.B. Moseley.
Previous ed.: Bioinformatics : a practical guide to the analysis of genes and proteins. c2005.
Includes bibliographical references and index.
Keywords: Computational biology -- Methods; Sequence analysis -- Methods; Base sequence; Databases, Nucleic Acid; Databases, Protein